Empirical risk factors in realized stock returns - Jiří Novák; Dalibor Petr (Charles University in Prague, Institute of Economic Studies (IES), 2009)
Measuring risk in the stock market context is one of the key challenges of modern finance. Despite of the substantial significance of the topic to investors and market regulators, there is a controversy over what risk factors should be used to price the assets or to determine the cost of capital. We empirically investigate the ability of several commonly proposed risk factors to predict Swedish stock returns. We consider the sensitivity of an asset returns to the variation in market returns, the market value of equity, the ratio of market value of equity to book value of equity and the short-term historical stock returns. We conclude that none of these factors is clearly significant for explaining stock returns at the Stockholm Stock Exchange, which casts doubt on their use as universal risk factors in various corporate governance contexts. It seems that the previously documented relationship is contingent on the data sample used and on the time period.
Keywords: G12; C21; 330; stock returns; asset pricing; risk; multifactor models; CAPM; size; book-to-market; momentum; Sweden; Kapitaleinkommen; CAPM; Risiko; Schätzung; Schweden